Biogeochemical Controls on the Release and Accumulation of Mn and As in Shallow Aquifers, West Bengal, India - Vega, Michael A.; Kulkarni, Harshad V.; Mladenov, Natalie; Johannesson, Karen; Hettiarachchi, Ganga M.; Bhattacharya, Prosun; Kumar, Naresh; Weeks, Joseph; Galkaduwa, Madhubhashini; Datta, Saugata (Frontiers in Environmental Science, 2017)
The prevalence of manganese (Mn) in Southeast Asian drinking water has recently become a topic of discussion, particularly when concurrent with elevated arsenic (As). Although Mn groundwater geochemistry has been studied, the link between dissolved organic matter (DOM) quality and Mn release is less understood. This work evaluates characteristics of DOM, redox chemistry, and the distribution of Mn within Murshidabad, West Bengal, India. Shallow aquifer samples were analyzed for cations, anions, dissolved organic carbon, and DOM properties using 3-dimensional fluorescence excitation emission matrices followed by parallel factor modeling analyses. Two biogeochemical regimes are apparent, separated geographically by the river Bhagirathi. East of the river, where Eh and nitrate (NO3-) values are low, humic-like DOM coexists with high dissolved Mn, As, and Fe. West of the river, lower dissolved As and Fe concentrations are coupled with more protein-like DOM and higher NO3- and Eh values. Dissolved Mn concentrations are elevated in both regions. Based on the distribution of available electron acceptors, it is hypothesized that groundwater east of the Bhagirathi, which are more reducing and enriched in dissolved Fe and Mn but depleted in NO3-, are chemically dominated by Mn(IV) / Fe(III) reduction processes. West of the river where NO3- is abundant yet dissolved Fe is absent, NO3- and Mn(IV) likely buffer redox conditions such that Eh values are not sufficiently reducing to release Fe into the dissolved phase. The co-occurrence of humic-like DOM with dissolved As, Fe, and Mn in the more reducing aquifers may reflect complex formation between humic DOM and metals, as well as electron shuttling processes involving humic DOM, which may enhance metal(loid) release. Saturation indices of rhodochrosite (MnCO3) suggest that precipitation is thermodynamically favorable in a greater proportion of the more reducing sites, however humic DOM–Mn complexes may be inhibiting MnCO3 precipitation. Where dissolved arsenic concentrations are low, it is postulated that Mn(IV) reduction is oxidizing As(III) to As(V), increasing the potential for re-adsorption of As(V) onto relatively stable, un-reduced or newly precipitated Fe-oxides. Manganese release appears to be independent of DOM quality, as it persists in both humic and protein-like DOM environments.